The Effect of VP3 Biofertilizer and Compost Application on Red Spinach (Amaranthus dubius) and Green Spinach (Amaranthus viridis) Yield and Quality: The Effect of VP3 Biofertilizer and Compost Application on Red Spinach (Amaranthus dubius) and Green Spinach (Amaranthus viridis) Yield and Quality - Arfarita, Novi; Masyhuri, Masyhuri; Sugiarto , Sugiarto; Higuchi, Takaya (Journal of Tropical Life Science, 2024)
VP3 biofertilizer is a biological agent that has been formulated in previous research. It was applied once with compost and has been tested on red spinach and green spinach in the greenhouse to see its effect on yield and quality (chlorophyll content, anthocyanins, and shelf life at room temperature). Red spinach and green spinach had shown a significantly different growth response to applying biological fertilizers. VP3 biofertilizer with compost had the highest yield effect but was not significantly different from the recommended Nitrogen Phosphate Potassium (NPK) and Effective Microorganism4(EM4) treatment with compost. The application of VP3 Biofertilizer with NPK fertilizer showed a darker color (higher chlorophyll and anthocyanin content) than the application of biological fertilizers, but the values ​​were not significantly different. The application of VP3 biofertilizer with compost affected the shelf life of both red spinach and green spinach. Spinach plants remained fresh at room temperature for three days of storage, while the other treatments lost freshness on the 3rd day after harvesting and even loosened the leaf on the 4th day after harvesting. Therefore, VP3 biofertilizer has potential to increase the yield and quality of spinach and other vegetable crops. The addition of the application period of VP3 biofertilizer needs to be carried out and observed to increase the yield and quality of plants further. Canonical Variate Analyses (CVA) can distinguish the grouping of treatments based on the selected parameter. Biplot assessment provides information on the strong relationship between the yield of green spinach and red spinach and a number of leaves, leaf area, and plant height. The application of VP3 biofertilizer with compost had a significant effect on the yield and quality and produced different effects between treatments, both in the case of green spinach and red spinach.